Beyond the Acronyms: Sport Diplomacy and the Classification of the International Olympic Committee. Issue 2 (2nd April 2016) - Postlethwaite, Verity; Grix, Jonathan
ABSTRACT: Diplomacy often finds itself reduced to actions centred on states. However, after the Cold War, international relations and diplomacy have expanded with different actors growing into significant roles, particularly in the increase of diplomatic relations in the context of sport. The classification and significance of other actors remains under-researched in relation to sport, with literature focusing more on the growth of new and varying practices of diplomacy. This analysis contends that there is a need to interrogate fundamental components of modern diplomacy—with the actor being the focus—more specifically the classification of sports organisations in diplomacy. It is relevant as a more accurate understanding of sports organisations will contribute to how diplomatic studies can analyse and evaluate modern diplomacy within the context of sport. The International Olympic Committee is the actor used to illustrate how problematic classifications currently in the academic literature translate into weak and reduced analysis and evaluation of its role and significance in diplomacy. As counterpoint, this analysis proposes an analytical framework of socio-legal theory that harnesses legal regulation as a benchmark to classify an actor's capacity within a society. In consequence, the IOC is as an active and significant contributor to the ever expanding and complex diplomatic environment and wider society.